1991
DOI: 10.1002/cne.903100306
|View full text |Cite
|
Sign up to set email alerts
|

Effects of prenatal protein deprivation on postnatal development of granule cells in the fascia dentata

Abstract: The effect of prenatal protein deprivation on the postnatal development of granule cells in the fascia dentata in the rat was studied at 15, 30, 90, and 220 days of age. The granule cells showed a significant reduction in cell size, decreased number of synaptic spines throughout their dendritic extent, and reduced complexity of dendritic branching in the outer two-thirds of the molecular layer. All of these deficits were present at 15 days and persisted throughout the study (220 days). The least deficits in sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
43
1
2

Year Published

1995
1995
2000
2000

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(49 citation statements)
references
References 45 publications
2
43
1
2
Order By: Relevance
“…These data are somewhat surprising in light of previous findings showing that the morphological properties of dentate granule cells are significantly altered in 6/25 rats (Cintra et al, 1990;1997;Díaz-Cintra et al, 1991). Clearly, the membrane alterations (e.g., decreases in soma diameter and decreases terminal dendritic extent) seen in the 6/25 rats are of insufficient magnitude to be reflected in such intrinsic membrane properties as membrane time constant and input resistance which were completely unchanged in the present study.…”
Section: Discussioncontrasting
confidence: 75%
See 1 more Smart Citation
“…These data are somewhat surprising in light of previous findings showing that the morphological properties of dentate granule cells are significantly altered in 6/25 rats (Cintra et al, 1990;1997;Díaz-Cintra et al, 1991). Clearly, the membrane alterations (e.g., decreases in soma diameter and decreases terminal dendritic extent) seen in the 6/25 rats are of insufficient magnitude to be reflected in such intrinsic membrane properties as membrane time constant and input resistance which were completely unchanged in the present study.…”
Section: Discussioncontrasting
confidence: 75%
“…These delays may in turn disrupt the development of appropriate afferent and efferent connections of these principal cells and lead to dysfunctional synaptic physiology. In addition, Golgi impregnation studies have demonstrated a decrease in the diameter of somata, density of dendritic spines and terminal dendritic arborization of dentate granule cells in response to prenatal protein malnutrition (Cintra et al, 1990;Díaz-Cintra et al, 1991). A recent study by Cintra et al (1997) demonstrated that CA1 pyramidal cells, in contrast, are largely spared, with the only significant change being a reduction in the density of dendritic spines in prenatally malnourished animals.…”
Section: Introductionmentioning
confidence: 91%
“…In this regard, projec tions from the visual cortex to the claustrum originating in the fourth layer and returning from the claustrum to the same cortical areas to layers IV and VI establishing a reciprocal modulator circuit, which may regulate senso ry influx to this zone [ 18], In undernourished rats the reduced dendritic arbor in the claus tral neurons may generate a deficient regula tory process that may be associated with inad equate locomotion [28,29] or with impaired visuospatial integration as observed in be 52 Escobar/Salas Neonatal Undemutrition and Claustrum Development havioral studies [30][31][32], This possibility is strengthened by data showing the high vulner ability of polysensory nervous structures to perinatal undernutrition in the thalamus [1,9], the amygdala [5], the hippocampus [3, 33,34], the cerebellar granular layer [35] and the intemeurons of the cerebral cortex [36], How ever, further morphological and behavioral studies will be needed in order to corroborate this proposal.…”
Section: Resultsmentioning
confidence: 96%
“…Certainly, brain weight is a gross measurement, and it would be desirable to perform a more detailed and specific morphological or neurochemical analysis of different brain regions in response to malnutrition and environmental factors since other studies have shown significant alterations in behavior-related regions of the brain (43)(44)(45)(46).…”
Section: Discussionmentioning
confidence: 99%